Students' metacognitive awareness and physics problem solving ability and correlation between them - Rahayu, Siti; Hertanti, Erina (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This study investigates the correlation between metacognitive awareness and students’ problem-solving ability level in direct current electricity concepts. This study is conducted in 2019 in one of the Senior High Schools in South Tangerang. There are 126 students of 12th grade majoring in Science (XII MIA) as the sample. A proportionate stratified random sampling technique chooses the sample. It is the choosing sample technique used randomly and proportionally that focused on the population's level. The method of the study is correlational. The study instruments are 45 Metacognitive Awareness Inventory (MAI) statements and seven essay questions of problem-solving ability test. The result of the Person Product Moment correlation and the significant test shows that metacognitive awareness has a positive and significant correlation with students’ problem-solving ability to direct current electricity concepts. Moreover, it is known that students’ metacognitive awareness and problem-solving ability are at a medium level.